Noble metal ions incorporated in lattice points of perovskites - water gas shift activity of BaCe1-xPtxO3-d - Jijil, Chamundi P.; Rajarajan, A. K.; Devi, R. Nandini (56th DAE-Solid State Physics Symposium (SSPS), 2012)
Recently precious metals supported on oxides were reported to be very promising catalysts for the lower-temperature WGS reaction. Here we report the synthesis of platinum doped barium cerate and its use as catalysts for WGS reaction. It has been found that maximum CO conversion was obtained at 350 degrees C which enhanced after the first cycle. XPS analysis shows that after the first cycle more ionic Platinum species are present on the surface of the catalyst. Neutron diffraction at room temperature shows that the oxygen vacancies are in the O2 position and increases with increasing Pt substitution.
Keywords: BaCeO3; Neutron diffraction; Platinum catalysis; WGS reaction

Novel porous silica encapsulated Au nanoreactors as peroxidase mimic for one-pot glucose detection - Samanta, Anupam; Dhar, Basab B.; Devi, R. Nandini (New Journal of Chemistry, 2012)
The peroxidase family of natural enzymes facilitate H2O2 reduction by one electron transfer through aromatic substrates, if chromogenic, they can be used in the colorimetric detection of H2O2 and subsequently glucose in tandem with glucose oxidase. Au nanoparticles encapsulated within porous silica exhibited peroxidase mimetic activity and kinetic parameter evaluation indicates an excellent affinity for H2O2. It is also shown to have a detection capability for glucose in very low concentrations and could be used for glucose detection in a one-pot assay. The material is synthesised by using cation-ended thiol-stabilised ultra small gold clusters as precursors. Removal of the thiols creates micropores within the silica, making this material unique in that the active centres are protected inside the silica, yet are accessible to reactant molecules. This characteristic makes the material ideal as a detection tool where attrition resistance will be advantageous.

Nanostructured donor-acceptor self assembly with improved photoconductivity - Saibal, B.; Ashar, A. Z.; Devi, R. Nandini; Narayan, K. S.; Asha, S. K. (ACS Applied Materials & Interfaces, 2014)
Nanostructured supramolecular donor-acceptor assemblies were formed when an unsymmetrical N-substituted pyridine functionalized perylenebisimide (UPBI-Py) was complexed with oligo(p-phenylenevinylene) (OPVM-OH) complementarily functionalized with hydroxyl unit and polymerizable methacrylamide unit at the two termini. The resulting supramolecular complex [UPBI-Py (OPVM-OH)](1.0) upon polymerization by irradiation in the presence of photoinitiator formed well-defined supramolecular polymeric nanostructures. Self-assembly studies using fluorescence emission from thin film samples showed that subtle structural changes occurred on the OPV donor moiety following polymerization. The 1:1 supramolecular complex showed red-shifted aggregate emission from both OPV (similar to 500 nm) and PBI (similar to 640 nm) units, whereas the OPV aggregate emission was replaced by intense monomeric emission (similar to 430 nrn) upon polymerizing the methacrylamide units on the OPVM-OH. The bulk structure was studied using wide-angle X-ray diffraction (WXRD). Complex formation resulted in distinct changes in the cell parameters of OPVM-OH. In contrast, a physical mixture of 1 mol each of OPVM-OH and UPBI-Py prepared by mixing the powdered solid samples together showed only a combination of reflections from both parent molecules. Thin film morphology of the 1:1 molecular complex as well as the supramolecular polymer complex showed uniform lamellar structures in the domain range <10 rim. The donor-acceptor supramolecular complex [UPBI-Py (OPVM-OH)](1.0) exhibited space charge limited current (SCLC) with a bulk mobility estimate of an order of magnitude higher accompanied by a higher photoconductivity yield compared to the pristine UPBI-Py. This is a very versatile method to obtain spatially defined organization of n and p-type semiconductor materials based on suitably functionalized donor and acceptor molecules resulting in improved photocurrent response using self-assembly.
Keywords: donor-acceptor; hydrogen bonding; oligo(p-phenylenevinylene); Perylenebisimide; photoconductivity; supramolecular polymeric nanostructures

Nitrogen-doped graphene interpenetrated 3D Ni-nanocages: efficient and stable water-to-dioxygen electrocatalysts - Dhavale, Vishal M.; Gaikwad, Sachin S.; George, Leena; Devi, R. Nandini; Kurungot, Sreekumar (Nanoscale, 2014)
Herein, we report the synthesis of a nitrogen-doped graphene (NGr) interpenetrated 3D Ni-nanocage (Ni-NGr) electrocatalyst by a simple water-in-oil (w/o) emulsion technique for oxidation of water to dioxygen. Correlation of adsorption of NGr and subsequent interpenetration through the specific surface plane of nickel particles as well as the concomitant interaction of N and C with Ni in the nano-regime has been investigated. Apart from the benefits of the synergistic interactions between Ni, N, and C, the overall integrity of the structure and its intra-molecular connectivity within the framework help in achieving better oxygen evolution characteristics at a significantly reduced overpotential. The engineered Ni-NGr nanocage displays a substantially low overpotential of similar to 290 mV at a practical current density of 20 mA cm(-2) in 0.1 M KOH. In comparison, NGr and Ni-particles as separate entities give overpotentials of similar to 570 and similar to 370 mV under similar conditions. Moreover, the long term stability of Ni-NGr was investigated by anodic potential cycling for 500 cycles and an 8.5% increment in the overpotential at 20 mA cm(-2) was observed. Additionally, a chronoamperometric test was performed for 15 h at 20 mA cm(-2), which highlights the better sustainability of Ni-NGr under the actual operating conditions. Finally, the quantitative estimation of evolved oxygen was monitored by gas chromatography and was found to be 70 mmol h(-1) g(-1) of oxygen, which is constant in the second cycle as well.

Nitrogen doping in oxygen-deficient Ca2Fe2O5: a strategy for efficient oxygen reduction oxide catalysts - Jijil, Chamundi P.; Lokanathan, Moorthi; Chithiravel, Sundaresan; Nayak, Chandrani; Bhattacharyya, Dibyendu; Jha, Shambhu Nath; Babu, P. D.; Kakade, Bhalchandra A.; Devi, R. Nandini (ACS Applied Materials and Interfaces, 2016)